Efficacy and Safety of Leflunomide for Refractory COVID-19: A Pilot Study - Wang, Qiang; Guo, Haipeng; Li, Yu; Jian, Xiangdong; Hou, Xinguo; Zhong, Ning; Fei, Jianchun; Su, Dezhen; Bian, Zhouyan; Zhang, Yi; Hu, Yingying; Sun, Yan; et al. (Frontiers in Pharmacology, 2021)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may persist in patients with coronavirus disease 2019 (COVID-19) despite receiving standard care. Methods: In this pilot study of hospitalized adult patients (≥18 years of age) with radiologically confirmed pneumonia and SARS-CoV-2 positive for more than 28 days despite standard care were assigned to receive standard of care (SOC, grp I) or leflunomide + SOC (grp 2). After 2 weeks, grp 1 and grp 2 patients who continued to be SARS-CoV-2-positive received leflunomide for 14 days while continuing SOC. The primary outcomes were the rate of and time to SARS-CoV-2 clearance and the 14-day and 30-day hospital discharge rate. Results: Twelve patients enrolled in grp 1 and 15 patients were in grp 2. The 14 days SARS-CoV-2 viral clearance rate was 80.0% (12/15) for grp 2 patients receiving leflunomide versus 16.7% for grp 1 patients (2/12) (P=0.002). By day 14, the median time to SARS-CoV-2 clearance was 6.0 days (range 1-12，IQR 1-12) for grp 2 patients. In grp 1, two patients converted to viral negative on days 1 and 6 (P=0.002). The 14-day discharge rate was 73.3% (11/15) for the grp 2 versus 8.3% (1/12) for grp 1 (P=0.001). The 30-day discharge rate was 100% (15/15) for the grp 2 versus 66.7% (8/12) for grp 1. No severe adverse events or deaths were reported. Conclusion: Leflunomide is effective in enhancing SARS-CoV-2 clearance and hospital discharge in refractory COVID-19 patients. The addition of leflunomide to SOC did not increase adverse events versus SOC. These preliminary observations underscore a need for a randomized clinical study of leflunomide in SARS-CoV-2 infection.